LEGAL ANALYSIS OF BANKRUPTCY DECISIONS IN CORPORATIONS DURING THE HOMOLOGATION PROCESS AND THEIR IMPACT ON LEGAL CERTAINTY - Sharon Dwi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study discusses legal issues regarding bankruptcy judgments issued against companies that are or have undergone the homologation process in the Suspension of Debt Payment Obligations (PKPU). In the bankruptcy legal system in Indonesia, homologation is the final stage of the PKPU which aims to provide an opportunity for debtors and creditors to reach a legally binding peace agreement. However, in practice, there is a missynchronization between the applicability of homologation and the possibility of bankruptcy applications, which raises debates about legal certainty and protection for the parties. This study uses a normative juridical approach with qualitative analysis methods of laws and regulations, doctrines, and case studies of court decisions. The results of the study show that although legally a bankruptcy judgment can be rendered against debtors who have undergone the homologation process, it can only be done if there is a real breach of the content of the agreement, and after the homologation is canceled through a valid legal mechanism. In addition, the implementation of the bankruptcy process that continues during the cassation of the bankruptcy decision that has not been decided in a binding manner can cause legal uncertainty that is detrimental to both debtors and creditors. For this reason, it is necessary to strengthen regulations and stricter judicial guidelines regarding the prohibition or limitation of bankruptcy filings as long as the homologation is still valid, as well as an automatic postponement mechanism for the bankruptcy process during legal proceedings. This is important to maintain the function of PKPU as a means of business rehabilitation and ensure the principles of legal certainty and justice for all parties.